Employee Non-compete Agreements, Gender, and Entrepreneurship - Marx, Matt (Organization Science, 2022)
I contribute to the literature on institutions, gender, and entrepreneurship by showing that macrolevel institutional policies that do not explicitly target women nonetheless discourage them from leveraging prior professional experience—their own and that of others—in founding new ventures. Most ventures fail, but chances of success are greater if founders can bring to bear their professional expertise. However, employee non-compete agreements enjoin workers from leaving their employer to found a rival business in the same industry. Thus, non-competes add legal risk to business risk. To the extent that women exhibit greater risk aversion, the threat of litigation from their ex-employer may act as a sharper brake on startup activity than for men. Examining all workers who were employed exclusively within 25 states and the District of Columbia from 1990 to 2014, I find that women subject to tighter non-compete policies were less likely to leave their employers and start rival businesses. Non-competes increase the risk of entrepreneurship by making it harder to hire talent with relevant experience, shifting women away from higher potential ventures. A review of thousands of filed lawsuits suggests that firms do not target women in non-compete cases. Rather, it appears that non-competes disproportionately discourage women from leveraging their professional networks in hiring the sort of talent necessary for high-growth startups to succeed.